P259 Correlation between the Mayo endoscopic scoring system for Ulcerative Colitis with histological and clinical outcomes. (30th January 2023) - Gibbons, E; Afridi, I; Sheehan, T; Smyth, C; Farrell, R; Hall, B; Kelly, O B
Abstract: Background: There is a growing body of literature demonstrating that persistent histological activity, despite endoscopic remission, is associated with increased risk of relapse in patients with UC. A recent meta-analysis reported a two-fold higher risk of relapse. The primary aim of this study was to examine the correlation of the Mayo endoscopic scoring system with histological outcomes and their association with flare/hospitalisation in the ensuing twelve months. Methods: We selected 87 random colonoscopies performed for UC surveillance/assessment during between 2017-2019. Adult patients with a complete colonoscopy were included. All reports were reviewed and blindly scored by 2 expert endoscopists using the Mayo scoring system. Histology was classified as normal, mild, moderate and severe by an experienced gastrointestinal histopathologist. Clinical/ IBD demographics, flare episodes and hospitalisations were recorded. Correlation between endoscopic and histologic activity was tested. Comparisons were made between patients in both endoscopic and histologic remission, those in endoscopic remission with histologic activity and those with both endoscopic and histologic activity. Results: 87 patients with UC (median age 50; M:F 46:41) were included. Patient groups were similar (p=ns for demographic variables). All levels of the Mayo scale (median score 1) were represented. 31/87 (36%) were in both endoscopic and histologic remission. Of these, 5/31 (16%) had a flare requiring steroids and change of treatment at 12 months. Only 5/87 (5.7%) were endoscopically in remission with persistent histologic disease. Of these 1/5 (20%) had a flare and required steroids at six months. Endoscopic activity was independently associated with steroid use/ flare at six months (Z= -.3.39, p= -.0006) and change in treatment (Z= -1.9, p= 0.03). Histologic activity was also independently associated with steroid use/ flare (Z= -2.9, p= 0.0038) and change in treatment (Z= -1.96, p= 0.025). Looking at the three groups together there was a significant difference in steroid use and flare, deep remission versus endoscopic remission histologic activity and endoscopic activity (Chi square = 11.6, p= 0.003 for steroids, Chi square = 7.39, p= 0.025 for flare). Conclusion: The therapeutic target in IBD has evolved over recent years from a focus on clinical remission to endoscopic remission. There is now a growing body of evidence that histological remission is an important endpoint. The extent that histologic remission affects outcomes is unclear to date. Further studies are required incorporating greater numbers of patients and robust histologic scoring systems.